The impact of aerobic and resistance training intensity on markers of neuroplasticity in health and disease - Hortobágyi, Tibor; Vetrovsky, Tomas; Balbim, Guilherme Moraes; Sorte Silva, Nárlon Cássio Boa; Manca, Andrea; Deriu, Franca; Kolmos, Mia; Kruuse, Christina; Liu-Ambrose, Teresa; Radák, Zsolt; Váczi, Márk; Johansson, Hanna; et al. (Ageing research reviews, 2022)
OBJECTIVE: To determine the effects of low- vs. high-intensity aerobic and resistance training on motor and cognitive function, brain activation, brain structure, and neurochemical markers of neuroplasticity and the association thereof in healthy young and older adults and in patients with multiple sclerosis, Parkinson's disease, and stroke. DESIGN: Systematic review and robust variance estimation meta-analysis with meta-regression. DATA SOURCES: Systematic search of MEDLINE, Web of Science, and CINAHL databases. RESULTS: Fifty studies with 60 intervention arms and 2283 in-analyses participants were included. Due to the low number of studies, the three patient groups were combined and analyzed as a single group. Overall, low- (g=0.19, p = 0.024) and high-intensity exercise (g=0.40, p = 0.001) improved neuroplasticity. Exercise intensity scaled with neuroplasticity only in healthy young adults but not in healthy older adults or patient groups. Exercise-induced improvements in neuroplasticity were associated with changes in motor but not cognitive outcomes. CONCLUSION: Exercise intensity is an important variable to dose and individualize the exercise stimulus for healthy young individuals but not necessarily for healthy older adults and neurological patients. This conclusion warrants caution because studies are needed that directly compare the effects of low- vs. high-intensity exercise on neuroplasticity to determine if such changes are mechanistically and incrementally linked to improved cognition and motor function.
Keywords: Resistance Training; Humans; Multiple Sclerosis; kognice; Cognition motor function; Aged; senioři; lidé; Biomarkers; neuroplasticita; Aging; odporový trénink; Neuronal Plasticity; biologické markery; roztroušená skleróza; Intensity Dose-response relationship; Exercise; cvičení; Cognition